Rapid Transitions: Experiences with Accessibility and Special Education during the COVID-19 Crisis - Long, Emily; Vijaykumar, Sruti; Gyi, Serena; Hamidi, Foad (Frontiers in Computer Science, 2021)
The ongoing outbreak of the Coronavirus Disease 2019 (COVID-19) and the ensuing preventative lock-down and shelter-in-place policies enacted around the world have caused unanticipated disruptions in the delivery of educational content and accessibility services to children, youth and adults with disabilities. The rapid move to online and remote learning, socialization, and therapeutic activities have surfaced some of the inadequacies of existing systems and infrastructures as well as opportunities for creating novel and accessible solutions. We conducted semi-structured remote interviews with nine special education teachers, therapists, community advocates, and individuals with disabilities to capture their perspectives on delivering services and supporting children and adults with disabilities and their families during the pandemic. Participants shared reflections on their experience and those who they serve during the initial phases of the COVID-19 crisis and the challenges and insights that this experience surfaced. Findings include a need to better support families in facilitating remote learning experiences for their children, developing tactile modes of engagement to complement online interactions, and the impact of a lack of contingency plans specifically to support people with disabilities and their families during crises. The participants also described the lack of clarity about the future as one of the most difficult aspects of the pandemic. We conclude with a discussion of these findings and directions for future research.